Dynamics of indicators of empirical research and biogeometric profile in wrestlers – veterans of sports with osteochondrosis of the lumbosacral spine - Гончаров, Олексій (Slobozhanskyi Herald of Science and Sport, 2018)
Oleksii Honcharov Purpose: to evaluate the effectiveness of the program of physical rehabilitation on the basis of studying the dynamics of indicators of empirical research, vertebro-neurological symptoms and biogeometric profile in wrestlers – veterans of sports with osteochondrosis of the lumbosacral spine. Material & Methods: theoretical analysis and generalization of literature data; use of diagnostic scales (visual analogue pain scale (VAS), scale of five-point evaluation of vertebro-neurological symptoms), determination of mobility of the lumbosacral spine, Schober's test, Tommyer test – fingers-floor test; methods of mathematical statistics. Results: based on the results of the study, a statistically significant dynamics of the parameters of the empirical study, the parameters of the biogeometric profile in the wrestlers – the veterans of the main group sport, was found in the course of physical rehabilitation according to the developed program with the application of therapeutic gymnastics, exercises in post-isometric relaxation. Conclusion: the results of the study confirmed the effectiveness of the comprehensive physical rehabilitation program developed by us, showed that a positive effect on the index of pain, vertebro-neurological symptoms, an increase in the amplitude of the spinal motion in both the sagittal and frontal planes.